The Role of Female Leadership in Times of Financial Crisis – an Analysis During the COVID-19 Pandemic - Sinha, Tanja (Copernican Journal of Finance & Accounting, 2024)
In 2020 the new COVID-19-virus brought an external shock to the stock markets. In this situation effective leadership was essential to bring companies through the crisis. Political observation showed that countries led by women managed the pandemic situation more effectively than those led by men. Therefore, the research objective of this article is to examine whether female leaders were also more successful to guide companies through the pandemic. Success in this study is defined as financial performance based on stock prices. To find out whether female managers showed a better financial performance during this crisis, this study examined all companies listed on the German Stock Exchange, which have at least 50 % women in the board. To compare this female managed companies to firms managed mainly by male managers, a market value weighted index for the female managed companies was conducted and compared to the German Stock Index DAX by looking at several financial key figures. The analysis of these key figures shows that female managed companies outperformed male managed companies in terms of return as well as risk in the year of the COVID-pandemic but were not able to keep their overperformance in the subsequent years. This may be an indicator that women are superior in leading a company through a crisis but suffer in terms of performance when times have calmed down.